Using Reproducing Kernel for Solving a Class of Fractional Order Integral Differential Equations - Zhiyuan Li; Meichun Wang; Yulan Wang; Jing Pang (Advances in Mathematical Physics)
This paper is devoted to the numerical scheme for a class of fractional order integrodifferential equations by reproducing kernel interpolation collocation method with reproducing kernel function in the form of Jacobi polynomials. Reproducing kernel function in the form of Jacobi polynomials is established for the first time. It is implemented as a reproducing kernel method. The numerical solutions obtained by taking the different values of parameter are compared; Schmidt orthogonalization process is avoided. It is proved that this method is feasible and accurate through some numerical examples.